Compass 2006 data analysis and reporting - Adams, Teresa M.; Juni, Emil (Midwest Regional University Transportation Center, 2007)
The Compass Operational Report is issued annually to identify the condition of Wisconsin?s state highway network. The primary audience for this report includes Operations Supervisors and Operations Managers at the Wisconsin Department of Transportation (WisDOT) and partner organizations including the 72 counties. Compass reports are used to understand trends and conditions, prioritize resources, and set future target condition levels for the state highway system. As more information is gathered, data will also be used to illustrate and understand the consequences of funding and policy shifts, and to demonstrate accountability to decision-makers at WisDOT and in the State Legislature. This report includes data on bridges, traveled ways, shoulders, drainage, roadsides, selected traffic devices, and specific aspects of winter operations. It is important to note information not contained in this report when using it to make decisions. It does not include measures of preventive maintenance, operational services (like traveler information and incident management), or electrified traffic assets (like signals and lighting). The first section of this report is an executive overview, a condensed version of the full report for executive managers in WisDOT.
106 p.
Keywords: Highway maintenance; Winter maintenance; Bridges; Data analysis; Road shoulders; Pavements; Trend (Statistics); Wisconsin; Traffic signs; Bridge maintenance; State highways